A unique case of gastrointestinal bleeding with splenomegaly - Can Gan; Shihang Tang (SAGE Open Medical Case Reports)
We present the case of a 61-year-old man with a 30-year history of iron-deficiency anemia and recurrent gastrointestinal bleeding, accompanied by splenomegaly and hypersplenism. Despite multiple endoscopy and imaging examinations, the source of bleeding remained elusive. The patient ultimately underwent exploratory laparotomy with splenectomy, which revealed a Meckel’s diverticulum with stale hemorrhage, along with congestive changes in the spleen. Following surgery, the patient experienced a complete resolution of symptoms with normalization of hematological parameters. This case highlights Meckel’s diverticulum as a rare cause of obscure gastrointestinal bleeding, with the unique presentation of splenomegaly due to extramedullary hematopoiesis.